2020
DOI: 10.25145/j.pasos.2020.18.008
|View full text |Cite
|
Sign up to set email alerts
|

Small and medium ‑sized accommodation managers and opportunities for water conservation

Abstract: To improve the environmental performance of small and medium -sized accommodation enterprises, it is important to understand the factors and motivations that move managers to adopt more efficient technologies and ecologically responsible practices. A sample of 18 independent family -run hotels and campsites were contacted in the mature tourist resort area of the Costa Brava (Spain). The research worked with a combination of surveys and semi -structured interviews directed at top managers. Saving water is revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…As a general rule, the study of personal values, ethics, altruistic attitudes, beliefs, worldview, and similar variables reveals unequivocally how managers who express greater environmental concern tend to be more receptive and proactive in adopting measures that encourage water saving in their facilities (Park et al 2014). Previous experience of management and especially of handling situations of hydrological crisis also influences decisions (Razumova et al 2016;Llausàs et al 2020). Despite the fact that these characteristics are inseparable from each individual, it has also been demonstrated that cultural and formative aspects mediate on them.…”
Section: Organizational Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a general rule, the study of personal values, ethics, altruistic attitudes, beliefs, worldview, and similar variables reveals unequivocally how managers who express greater environmental concern tend to be more receptive and proactive in adopting measures that encourage water saving in their facilities (Park et al 2014). Previous experience of management and especially of handling situations of hydrological crisis also influences decisions (Razumova et al 2016;Llausàs et al 2020). Despite the fact that these characteristics are inseparable from each individual, it has also been demonstrated that cultural and formative aspects mediate on them.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…Sometimes managers of small hotels and family-run hostels have been attributed a greater awareness and commitment to environmental care, because of a more direct engagement with the environment and the local community, which would result in a greater feeling of attachment and co-responsibility (Bohdanowicz 2006;Park et al 2014). However, other findings suggest that SMAEs tend to be less active in implementing improvements; their managers are more skeptical about the benefits their actions can bring; they can shift the burden of responsibility for solving environmental problems to other stakeholders; and they face a shortage of financial resources and time to devote to formal environmental management initiatives for water or energy (Hillary 2004;Torres-Bagur et al 2019;Llausàs et al 2020). There is ample evidence that the largest businesses, and especially the large hotel chains, are the most active in formally adopting policies and plans of action and training in environmental sustainability through what are known as Environmental Management Systems (EMS) (Mensah 2006;Rahman et al 2012).…”
Section: Organizational Factorsmentioning
confidence: 99%
See 2 more Smart Citations